Enzyme-assisted extraction of phenolic compounds from murucizeiro leaves (Byrsonima crassifolia) - Oliveira, Johnatt Allan Rocha; Komesu, Andrea; Martins, Luiza Helena Da Silva; Rogez, Hervé; Pena, Rosinelson da Silva (Scientia Plena, 2020)
The aim of this work was to evaluate the enzyme-assisted extraction of phenolic compounds from murucizeiro leaves (Byrsonima crassifolia) employing response surface methodology (RSM), in order to determine the best extraction conditions. The chemical composition of the leaves and characteristics of the enzymes were determined. The independent variables were temperature (19 to 70°C), pH (2.4 to 7.5) and reaction time (19 to 220 minutes). A conventional and optimized triple extraction with organic solvents was used as control. As result to solvent extraction was observed 73.28 mg of gallic acid equivalents (GAE) g-1 DM, while under the best condition for enzyme-assisted extraction (temperature: 60°C; pH: 4.5; and time: 220 min), the concentration was 90.65 mg GAE g-1. The independent variables significant were: temperature, pH and log time at the linear level and temperature at the quadratic level. A similar methodology could be encouraged for other natural products rich in phenolic compounds.